P-129 Recognising delirium in a palliative care inpatient unit-are we doing enough?. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Matthews, Sam; Kean, Rebecca; Mckenna, Emer; Chatha, Salman Rafique
Abstract : Background: As a hospice we had introduced several initiatives to improve care of inpatients including sepsis awareness and the butterfly scheme which support patients who are confused without a formal diagnosis of dementia. Amongst palliative inpatients, a recent systematic review found that occurrence rates varied by up to 30% on admission, during admission, and the weeks and hours before death. Aim: We wanted to understand within our inpatient setting how frequently confusion is an issue on admission, how we are detecting delirium and are we looking for reversibility. Between one-third and one-half of delirium cases are potentially reversible. Results: We conducted a baseline retrospective audit of admission records over March 2019. 39 notes meet criteria where patient had not died within 24 hours of admission. 25% (10) remained unconfused within 24 hours before death. 7% (3) were confused on admission but were reversed with medication changes and interventions such as antibiotics or oxygen suggesting delirium a feature of agitation and successfully went home. None of these patients has underlying brain pathology. 41% (16) who were confused died despite a small improvement in confusion. Delirium and accurately describing acute confusion was sporadic. Only one patient who remained confused from admission was discharged. Outcome: We implemented a lunch and learn mandatory programme for all clinical staff and introduced the 4AT tool and delirium checklist as first steps to earlier recognition and identification of reversible factors. We have also created a family and patient leaflet explaining what delirium is and how it can be managed. Conclusion: There is evidence of change in practice already within the nursing staff approach to monitoring and managing confused patients. We plan to re-audit in October and introduce the same learning programme for all community staff especially Hospice at Home healthcare assistants to enhance detection of delirium within the home setting.